Two Novel Neuropeptides in Innervation of the Salivary Glands of the Black-Legged Tick, Ixodes scapularis: Myoinhibitory Peptide and SIFamide - ŠIMO, LADISLAV (2009)
The peptidergic signaling system is an ancient cell–cell communication mechanism that is involved in numerous behavioral and physiological events in multicellular organisms. We identified two novel neuropeptides in the neuronal projections innervating the salivary glands of the blacklegged tick, Ixodes scapularis (Say, 1821). Myoinhibitory peptide (MIP) and SIFamide immunoreactivities were colocalized in the protocerebral cells and their projections terminating on specific cells of salivary gland acini (types II and III). Immunoreactive substances were identified by matrix-assisted laser desorption/ionization-time of flight (MALDITOF) analysis: a 1,321.6-Da peptide with the sequence typical for MIP (ASDWNRLSGMWamide) and a 1,395.7-Da SIFamide (AYRKPPFNGSIFamide), which are highly conserved among arthropods. Genes encoding these peptides were identified in the available Ixodes genome and expressed sequence tag (EST) database. In addition, the cDNA encoding the MIP prepropeptide was isolated by rapid amplification of cDNA ends (RACE). In this report, we describe the anatomical structure of specific central neurons innervating salivary gland acini and identify different neuropeptides and their precursors expressed by these neurons. Our data provide evidence for neural control of salivary gland by MIP and SIFamide from the synganglion, thus leading a basis for functional studies of these two distinct classes of neuropeptides.